Climate Change Budget Tagging : A Review of International Experience - World Bank (World Bank, Washington, DC, 2021)
The purpose of this report is to provide development practitioners and government officials with an understanding of the context and key design features of climate budget tagging initiatives. It is based on a review of 18 climate budgeting tagging methodologies as well as key informant interviews with practitioners during 2020. The review is structured into five sections. The first draws lessons from three precursors of climate expenditure tagging: poverty tagging, gender-budget tagging, and budgeting for international development goals. The second provides an overview of climate finance reporting methodologies and climate expenditure reviews supported by international organizations. The third reviews technical and institutional aspects of the climate budget tagging methodologies and practices of a number of national governments. The fourth explores links between climate budget tagging and the green bond frameworks used to mobilize climate finance. The final section discusses the benefits of and challenges in implementing a climate change tagging system and also presents lessons learned from experience in budget tagging in general and its application to climate change in particular. The report does not assess the effectiveness of climate budget tagging, as this would require a more thorough and long-term evaluation.